Striatal-insula circuits in cocaine addiction: implications for impulsivity and relapse risk. (4th November 2013) - McHugh, Meredith J.; Demers, Catherine H.; Braud, Jacquelyn; Briggs, Richard; Adinoff, Bryon; Stein, Elliot A.
Abstract: Background : Dysregulated striatal functioning coupled with executive control deficits arising from abnormal frontal cortical function are considered key mechanisms in the development and maintenance of cocaine addiction. The same features are thought to underlie high trait impulsivity observed in cocaine-addicted populations. Objectives : Employing resting state functional connectivity, the current study sought to identify cortico-striatal circuit alterations in cocaine addiction and examine the degree to which circuit connectivity contributes to relapse risk and impulsivity among cocaine-addicted individuals. Methods: Whole-brain resting-state functional magnetic resonance imaging connectivity was assessed in 45 cocaine-addicted individuals relative to 22 healthy controls using seed volumes in the left and right caudate, putamen and nucleus accumbens. Cocaine-addicted individuals completed scans in the final week of a 2–4 weeks residential treatment episode. Relapse by day 30 post-discharge served to separate cocaine-addicted individuals into relapse and non-relapse groups. All participants completed the Barratt Impulsivity Scale (BIS-11a). Results : Cocaine-addicted individuals exhibited reduced positive connectivity between the bilateral putamen and posterior insula and right postcentral gyrus. Group differences were primarily driven by reduced connectivity in relapse individuals relative to controls. No relapse versus non-relapse differences emerged. Impulsivity (BIS-11a) was higher in cocaine-addicted participants, an effect that was partially mediated by reduced putamen-posterior insula connectivity in this group. Conclusion : Cocaine addiction, relapse risk and impulsivity were associated with reduced connectivity in putamen-posterior insula/postcentral gyrus circuits implicated in temporal discounting and habitual responding. Findings provide new insight into the neurobiological mechanisms underlying impulsivity and relapse in cocaine addiction.